Formaldehyde-free flame-retardant adhesive, flame-retardant wood board and preparation method

Through the preparation of soy protein modification and high viscosity antibacterial crosslinking agent, combined with current crosslinking composite technology, the environmental and health problems of traditional adhesives are solved, and the realization of high strength, thermal stability and flame retardant effect of the antibacterial adhesive is achieved. .

CN119463758AActive Publication Date: 2025-02-18SUQIAN HEXINYIZHIYUAN TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411641914.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Traditional adhesives use formaldehyde as crosslinking agents, which lead to environmental pollution and health risks. Environmentally friendly materials without aldehyde flame retardant adhesives rely on petroleum resources, and have non-renewability and high production costs. Bio-based adhesives have poor thermal stability, are prone to mold and have poor compatibility.

Method used

Through soy protein modification treatment and the preparation of high-viscosity antibacterial crosslinking agents, combined with current crosslinking composite technology, a dehyde-free flame-retardant adhesive with good flame retardant effect is prepared.

Benefits of technology

It significantly improves the glue strength, thermal stability and flame retardant properties, reduces dependence on petroleum resources, and is environmentally friendly and safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463758A_ABST
    Figure CN119463758A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of artificial boards, in particular to a formaldehyde-free flame-retardant adhesive, a flame-retardant wood board and a preparation method. Comprising the following steps: modifying soybean protein; preparing a high-viscosity antibacterial cross-linking agent; and carrying out current cross-linking compounding on the adhesive. The high-strength modifier is prepared, then the high-strength modifier, ammonia water and soybean meal particles are subjected to a condensation reflux reaction subsequently, in the process, ammonia molecules serve as a nucleophilic reagent to attack carbon atoms in itaconic anhydride in the high-strength modifier, an intermediate is formed, water molecules are lost, and itaconic acid is generated; the emulsifying property of the high-strength modifier is improved, so that the high-strength modifier and the soybean meal particles are subjected to a polymerization reaction better at a high temperature to form nano particles which take the soybean meal particles as cores and the high-strength modifier as shells, and the nano particles have good uniformity and dispersity; and the bonding strength and the waterproof performance of the formaldehyde-free flame-retardant adhesive applied to plywood are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial boards, and in particular to a formaldehyde-free flame-retardant adhesive, a flame-retardant wood board and a preparation method thereof. Background Art

[0002] my country is the world's largest producer, consumer and international trader of wood-based panels, with an annual output accounting for more than 50% of the world's total output. However, traditional adhesives usually use formaldehyde as a cross-linking agent, which not only pollutes the environment but also poses a potential threat to human health. In order to meet the requirements of low formaldehyde emissions, market demand has prompted the research and development of formaldehyde-free adhesives to receive increasing attention.

[0003] Formaldehyde-free flame-retardant adhesives replace the formaldehyde component in traditional adhesives with environmentally friendly materials such as polyvinyl alcohol, polyurethane, and epoxy resin. These materials can not only provide good bonding properties, but can also be combined with flame retardant additives (such as inorganic phosphates, nitrogen compounds, etc.) to effectively improve the flame retardant properties of wood products and extend their service life. However, these environmentally friendly materials are often synthetic resins, most of which are highly dependent on petroleum resources, are non-renewable, and have high production costs.

[0004] Bio-based adhesives are a type of natural polymer adhesive made from degradable or renewable biomass raw materials such as starch, plant protein, tannin and lignin, which are used to replace synthetic resins. They have the advantages of abundant sources and low prices. However, these natural polymer materials often have poor thermal stability, are prone to mold, and have poor compatibility with inorganic substances, resulting in poor performance of the prepared adhesives. Summary of the invention

[0005] In order to solve the above technical defects, the present invention has developed an environmentally friendly and safe formaldehyde-free flame-retardant adhesive with high adhesive strength, good thermal stability and flame retardant effect. The flame-retardant wood board prepared using the formaldehyde-free flame-retardant adhesive has excellent bonding strength, bonding stability and flame retardant properties.

[0006] Furthermore, the present application provides a method for preparing a formaldehyde-free flame retardant adhesive, comprising the following steps:

[0007] S1: Modification of soy protein

[0008] Divinylbenzene and itaconic anhydride are mixed, and then isoamyl acetate is added and stirred, and then azobisisobutyronitrile is added and nitrogen is introduced, and then the mixture is heated for reaction and then centrifuged to obtain a solid substance, and then the solid substance is washed and dried to obtain a high-strength modifier, and the soybean meal is ultrafinely ground to obtain soybean meal particles, and the high-strength modifier and deionized water are added to a container equipped with a stirring device and a condensing device, and then ammonia water is added, and then the soybean meal particles are added after stirring, and nitrogen is introduced in a stirring state, and then the mixture is heated and stirred to obtain modified soybean meal;

[0009] S2: Preparation of highly viscous antibacterial crosslinkers

[0010] Put titanium acetylacetonate in a container, add toluene and stir, then add zinc borate powder, heat and stir, and then perform rotary evaporation to obtain surface-modified zinc borate, put the surface-modified zinc borate and polyethylene-vinyl acetate into a high-speed mixer, heat and stir, and obtain a high-viscosity antibacterial cross-linking agent;

[0011] S3: Current cross-linking compounding of adhesive

[0012] The modified soybean meal, expanded graphite and high-viscosity antibacterial cross-linking agent are mixed evenly, then placed in a container equipped with electrodes, powered on, and alternately powered on and stirred at a fixed frequency to obtain a cross-linked soybean meal. The cross-linked soybean meal, inositol phosphate, sodium alginate and polyamide are mixed and placed in a container, and heated and stirred for a second time to obtain a formaldehyde-free flame retardant adhesive.

[0013] Furthermore, step S1, the modification treatment of soybean protein, comprises the following steps:

[0014] S1.1: Divinylbenzene and itaconic anhydride containing 0.1-0.15wt% of tert-butylcatechol as a stabilizer are mixed in a mass ratio of 1:(0.8-0.9) in a container, and then 2-3 times the mass of isoamyl acetate is added and stirred evenly, and then 1-2wt% of azobisisobutyronitrile is added and nitrogen is introduced for 25-30 minutes, and then reacted at 70-75°C for 10-12 hours, and solid matter is obtained after centrifugation, washed with isoamyl acetate 2-3 times and then with petroleum ether 2-3 times, and then dried in a vacuum drying oven at 40-45°C to constant weight to obtain a high-strength modifier;

[0015] S1.2: The soybean meal is placed in an ultrafine grinder and crushed to a particle size of 10-20 μm to obtain soybean meal microparticles. 2-3 parts by weight of a high-strength modifier and 40-50 parts by weight of deionized water are added to a container equipped with a stirring device and a condensing device, and then 0.6-0.9 parts by weight of ammonia water are added. After stirring for 20-30 minutes, 9-12 parts by weight of soybean meal microparticles are added. Nitrogen is bubbled through the mixture under stirring for 20-25 minutes. The mixture is then heated to 60-65°C and stirred at a stirring speed of 200-300 rpm for 2-3 hours to obtain modified soybean meal.

[0016] Furthermore, the preparation of the high-viscosity antibacterial cross-linking agent in step S2 comprises the following steps:

[0017] S2.1: 0.2-0.3 parts by weight of titanium acetylacetonate is placed in a container, 6-8 parts by weight of toluene is added and stirred for 20-30 minutes, then 3-4 parts by weight of zinc borate powder is added, heated to 40-50° C. and stirred for 30-35 minutes, then placed in a rotary evaporator at a temperature of 70-75° C. to evaporate and remove the toluene, to obtain surface-modified zinc borate;

[0018] S2.2: Place the surface-modified zinc borate and polyethylene-vinyl acetate in a mass ratio of 1:(20-30) into a high-speed mixer, stir at 60-65° C. and a stirring speed of 180-240 rpm for 1-1.5 hours to obtain a high-viscosity antibacterial cross-linking agent.

[0019] Furthermore, the current cross-linking and compounding of the adhesive in step S3 comprises the following steps:

[0020] S3.1: The modified soybean meal, expanded graphite and high-viscosity antibacterial cross-linking agent are mixed and stirred uniformly at a mass ratio of 1: (0.02-0.03): (0.15-0.2), and the stirring speed is set to 220-250rpm. Then, the mixture is placed in a container, and a power supply is turned on. The voltage is increased to 25-30V at a rate of 3-5V / min, and the voltage is maintained. The power supply is turned off and stirred for 10-15S every 4-6 minutes, and then the power supply is turned on again and directly energized at a voltage of 25-30V for 25-30 minutes to obtain a cross-linked soybean meal.

[0021] S3.2: Mix 15-20 parts by weight of cross-linked soybean meal, 1-2 parts by weight of inositol phosphate, 0.5-1 parts by weight of sodium alginate and 1-1.2 parts by weight of polyamide in a container, heat to 50-60°C, stir for 0.5-1 hour, then heat to 80-85°C, stir for 1-2 hours to obtain a formaldehyde-free flame retardant adhesive.

[0022] Furthermore, the soybean meal in step S1.2 is the product obtained by hot pressing soybeans to extract oil.

[0023] Furthermore, in step S2.2, the vinyl acetate content of the polyethylene-vinyl acetate is 40-45%.

[0024] Furthermore, the container in step S3.1 is a rectangular parallelepiped, with a length, width and height of 20 cm, 10 cm and 10 cm respectively, and 316 stainless steel electrodes are installed on the inner walls on both sides, which are respectively connected to the positive and negative poles of the power supply.

[0025] Furthermore, the present application provides a formaldehyde-free flame-retardant adhesive, which is prepared by the above-mentioned method for preparing a formaldehyde-free flame-retardant adhesive.

[0026] Furthermore, the present application provides a flame-retardant wooden board, which includes a substrate and a formaldehyde-free flame-retardant adhesive coated on the upper and lower surfaces of the substrate, the substrate is a poplar veneer, and the formaldehyde-free flame-retardant adhesive is the formaldehyde-free flame-retardant adhesive described in any one of claims 1-7.

[0027] Furthermore, the present application provides a method for preparing a flame-retardant wood board made from the above-mentioned formaldehyde-free flame-retardant adhesive, comprising the following steps:

[0028] Use manual gluing method to apply formaldehyde-free flame retardant adhesive at 200g / m 2 Apply glue to the upper and lower surfaces of the poplar veneer with a certain amount of glue. After the gluing is completed, leave it for 8 minutes, then assemble it with two poplar veneers on the outside and one poplar veneer on the inside, and then put it in a hot press for 10 minutes. The hot pressing temperature is 130℃ and the hot pressing pressure is 1.2MPa. After pressing, cool it for use.

[0029] The beneficial effects are as follows: 1. The high-strength modifier is obtained by reacting divinylbenzene and itaconic anhydride under the action of an initiator azobisisobutyronitrile, and then a condensation reflux reaction is carried out with ammonia water and soybean meal particles. In this process, ammonia molecules act as nucleophiles to attack carbon atoms in itaconic anhydride in the high-strength modifier, form intermediates and lose water molecules to generate itaconic acid, thereby increasing the emulsification performance of the high-strength modifier, thereby better polymerizing with soybean meal particles at high temperatures to form nanoparticles with soybean meal particles as cores and the high-strength modifier as shells, and having good uniformity and dispersibility, and significantly improving the bonding strength and waterproof performance of the formaldehyde-free flame retardant adhesive when applied to plywood.

[0030] 2. The present invention cross-links modified soybean meal, expanded graphite and a high-viscosity antibacterial cross-linking agent by mixing them under electric current. Under the action of the electric current, the protein active groups in the modified soybean meal are fully exposed, and the functional groups of the high-viscosity antibacterial cross-linking agent are also activated under the action of the electric current to generate free radicals, which fully undergo cross-linking reactions with the molecular chains of the modified soybean meal and the expanded graphite to form a three-dimensional network structure. The cross-linked soybean meal obtained not only has good bonding strength, but also has significantly enhanced thermal stability, thereby greatly improving the dry bonding strength and wet boiling water-resistant bonding strength of the subsequently prepared plywood.

[0031] 3. The present invention heats zinc borate powder in toluene in which titanium acetylacetonate is dissolved, and then performs rotary evaporation to remove the toluene, thereby obtaining surface-modified zinc borate. The surface-modified zinc borate is then mixed with polyethylene-vinyl acetate to obtain a high-viscosity antibacterial cross-linking agent. During this process, titanium acetylacetonate is first combined with zinc borate to form zinc borate with a functionalized surface, thereby improving the compatibility of zinc borate in organisms, so that zinc borate can fully exert its antibacterial and flame-retardant effects in the formaldehyde-free flame-retardant adhesive, and avoids the decrease in stability of the formaldehyde-free flame-retardant adhesive caused by the subsequent addition of a flame-retardant system mainly composed of phosphoinositide, sodium alginate and polyamide. The obtained formaldehyde-free flame-retardant adhesive has excellent thermal stability, antibacterial properties and flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a flow chart of a method for preparing a formaldehyde-free flame-retardant adhesive used in an embodiment of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Embodiment 1: A formaldehyde-free flame retardant adhesive, a flame retardant wood board and a preparation method thereof, such as Figure 1 As shown, the following steps are included:

[0035] S1: Modification of soy protein

[0036] S1.1: Divinylbenzene and itaconic anhydride containing 0.1wt% of tert-butylcatechol as a stabilizer are mixed in a mass ratio of 1:0.8 in a container, and then 2 times the mass of isoamyl acetate is added and stirred evenly, and then 1wt% of azobisisobutyronitrile is added and nitrogen is introduced for 25 minutes, and then reacted at 70°C for 10 hours, and solid matter is obtained after centrifugation, washed twice with isoamyl acetate and then washed twice with petroleum ether, and then dried in a vacuum drying oven at 40°C to constant weight to obtain a high-strength modifier;

[0037] S1.2: The soybean meal after hot pressing and oil extraction is placed in an ultrafine grinder and crushed to a particle size of 10 μm to obtain soybean meal microparticles. 2 parts by weight of a high-strength modifier and 40 parts by weight of deionized water are added to a container equipped with a stirring device and a condensing device, and then 0.6 parts by weight of ammonia water are added. After stirring for 20 minutes, 9 parts by weight of soybean meal microparticles are added, and nitrogen is bubbled while stirring for 20 minutes. Then the temperature is raised to 60°C and stirred at a stirring speed of 200 rpm for 2 hours to obtain modified soybean meal.

[0038] S2: Preparation of highly viscous antibacterial crosslinkers

[0039] S2.1: 0.2 parts by weight of titanium acetylacetonate is placed in a container, 6 parts by weight of toluene is added and stirred for 20 minutes, then 3 parts by weight of zinc borate powder is added, heated to 40°C and stirred for 30 minutes, then placed in a rotary evaporator at 70°C to evaporate and remove the toluene, to obtain surface-modified zinc borate;

[0040] S2.2: Surface-modified zinc borate and polyethylene-vinyl acetate are put into a high-speed mixer at a mass ratio of 1:20, the vinyl acetate content in the polyethylene-vinyl acetate is 40%, and stirred at 60°C at a stirring speed of 180 rpm for 1 hour to obtain a high-viscosity antibacterial cross-linking agent.

[0041] S3: Current cross-linking compounding of adhesive

[0042] S3.1: The modified soybean meal, expanded graphite and high-viscosity antibacterial cross-linking agent were mixed and stirred at a mass ratio of 1:0.02:0.15, and the stirring speed was set to 220 rpm. Then, the mixture was placed in a rectangular container with a length, width and height of 20 cm, 10 cm and 10 cm respectively, and 316 stainless steel electrodes connected to the positive and negative poles of the power supply were installed on the inner walls of both sides. The power was turned on, and the voltage was increased to 25 V at a rate of 3 V / min and then maintained. The power was turned off and stirred for 10 seconds every 4 minutes, and then it was turned on again and powered on directly at a voltage of 25 V for 25 minutes to obtain cross-linked soybean meal;

[0043] S3.2: Mix 15 parts by weight of cross-linked soybean meal, 1 part by weight of inositol phosphate, 0.5 part by weight of sodium alginate and 1 part by weight of polyamide in a container, heat to 50°C, stir for 0.5 hour, then heat to 80°C, stir for 1 hour to obtain a formaldehyde-free flame retardant adhesive.

[0044] Based on the formaldehyde-free flame-retardant adhesive prepared by the method for preparing the formaldehyde-free flame-retardant adhesive, the present application provides a flame-retardant wooden board, comprising a substrate and a formaldehyde-free flame-retardant adhesive coated on the upper and lower surfaces of the substrate, wherein the substrate is a poplar veneer; the method for preparing the flame-retardant wooden board comprises the following steps:

[0045] Use manual gluing method to apply formaldehyde-free flame retardant adhesive at 200g / m 2 Apply glue to the upper and lower surfaces of the poplar veneer with a certain amount of glue. After the gluing is completed, leave it for 8 minutes, then assemble it with two poplar veneers on the outside and one poplar veneer on the inside, and then put it in a hot press for 10 minutes. The hot pressing temperature is 130℃ and the hot pressing pressure is 1.2MPa. After pressing, cool it for use.

[0046] Embodiment 2: A formaldehyde-free flame retardant adhesive, a flame retardant wood board and a preparation method thereof, such as Figure 1 As shown, the following steps are included:

[0047] S1: Modification of soy protein

[0048] S1.1: Divinylbenzene and itaconic anhydride containing 0.15wt% of tert-butylcatechol as a stabilizer are mixed in a mass ratio of 1:0.9 in a container, and then 3 times the mass of isoamyl acetate is added and stirred evenly, and then 2wt% of azobisisobutyronitrile is added and nitrogen is introduced for 25 minutes, and then reacted at 70°C for 10 hours, and solid matter is obtained after centrifugation, washed twice with isoamyl acetate and then washed twice with petroleum ether, and then dried in a vacuum drying oven at 40°C to constant weight to obtain a high-strength modifier;

[0049] S1.2: The soybean meal after hot pressing and oil extraction is placed in an ultrafine grinder and crushed to a particle size of 10 μm to obtain soybean meal microparticles. 3 parts by weight of a high-strength modifier and 50 parts by weight of deionized water are added to a container equipped with a stirring device and a condensing device, and then 0.9 parts by weight of ammonia water are added. After stirring for 20 minutes, 12 parts by weight of soybean meal microparticles are added, and nitrogen is bubbled while stirring for 20 minutes. Then the temperature is raised to 60°C and stirred at a stirring speed of 200 rpm for 2 hours to obtain modified soybean meal.

[0050] S2: Preparation of highly viscous antibacterial crosslinkers

[0051] S2.1: 0.3 parts by weight of titanium acetylacetonate is placed in a container, 8 parts by weight of toluene is added and stirred for 20 minutes, then 4 parts by weight of zinc borate powder is added, the mixture is heated to 40°C and stirred for 30 minutes, and then the mixture is placed in a rotary evaporator at 70°C to evaporate and remove the toluene to obtain surface-modified zinc borate;

[0052] S2.2: Surface-modified zinc borate and polyethylene-vinyl acetate are put into a high-speed mixer at a mass ratio of 1:30, the vinyl acetate content in the polyethylene-vinyl acetate is 45%, and stirred at 60°C at a stirring speed of 180 rpm for 1 hour to obtain a high-viscosity antibacterial cross-linking agent.

[0053] S3: Current cross-linking compounding of adhesive

[0054] S3.1: The modified soybean meal, expanded graphite and high-viscosity antibacterial cross-linking agent were mixed and stirred at a mass ratio of 1:0.03:0.2, and the stirring speed was set to 220 rpm. Then, the mixture was placed in a rectangular container with a length, width and height of 20 cm, 10 cm and 10 cm respectively, and 316 stainless steel electrodes connected to the positive and negative poles of the power supply were installed on the inner walls of both sides. The power was turned on, and the voltage was increased to 25 V at a rate of 3 V / min and then maintained. The power was turned off and stirred for 10 seconds every 4 minutes, and then it was turned on again and powered on directly at a voltage of 25 V for 25 minutes to obtain cross-linked soybean meal;

[0055] S3.2: Mix 20 parts by weight of cross-linked soybean meal, 2 parts by weight of inositol phosphate, 1 part by weight of sodium alginate and 1.2 parts by weight of polyamide in a container, heat to 50°C, stir for 0.5 hour, then heat to 80°C, stir for 1 hour to obtain a formaldehyde-free flame retardant adhesive.

[0056] Based on the formaldehyde-free flame-retardant adhesive prepared by the method for preparing the formaldehyde-free flame-retardant adhesive, the present application provides a flame-retardant wooden board, comprising a substrate and a formaldehyde-free flame-retardant adhesive coated on the upper and lower surfaces of the substrate, wherein the substrate is a poplar veneer; the method for preparing the flame-retardant wooden board comprises the following steps:

[0057] Use manual gluing method to apply formaldehyde-free flame retardant adhesive at 200g / m 2 Apply glue to the upper and lower surfaces of the poplar veneer with a certain amount of glue. After the gluing is completed, leave it for 8 minutes, then assemble it with two poplar veneers on the outside and one poplar veneer on the inside, and then put it in a hot press for 10 minutes. The hot pressing temperature is 130℃ and the hot pressing pressure is 1.2MPa. After pressing, cool it for use.

[0058] Embodiment 3: A formaldehyde-free flame retardant adhesive, a flame retardant wood board and a preparation method thereof, such as Figure 1 As shown, the following steps are included:

[0059] S1: Modification of soy protein

[0060] S1.1: Divinylbenzene and itaconic anhydride containing 0.1wt% of tert-butylcatechol as a stabilizer are mixed in a mass ratio of 1:0.8 in a container, and then 2 times the mass of isoamyl acetate is added and stirred evenly, and then 1wt% of azobisisobutyronitrile is added and nitrogen is introduced for 30 minutes, and then reacted at 75°C for 12 hours, and solid matter is obtained after centrifugation, washed with isoamyl acetate 3 times and then with petroleum ether 3 times, and then dried in a vacuum drying oven at 45°C to constant weight to obtain a high-strength modifier;

[0061] S1.2: The soybean meal after hot pressing and oil extraction is placed in an ultrafine grinder and crushed to a particle size of 20μm to obtain soybean meal microparticles. 2 parts by weight of a high-strength modifier and 40 parts by weight of deionized water are added to a container equipped with a stirring device and a condensing device, and then 0.6 parts by weight of ammonia water are added. After stirring for 30 minutes, 9 parts by weight of soybean meal microparticles are added, and nitrogen is bubbled while stirring for 25 minutes. Then the temperature is raised to 65°C and stirred at a stirring speed of 300rpm for 3 hours to obtain modified soybean meal.

[0062] S2: Preparation of highly viscous antibacterial crosslinkers

[0063] S2.1: 0.2 parts by weight of titanium acetylacetonate is placed in a container, 6 parts by weight of toluene is added and stirred for 30 minutes, then 3 parts by weight of zinc borate powder is added, heated to 50°C and stirred for 35 minutes, then placed in a rotary evaporator at 75°C to evaporate and remove the toluene, to obtain surface-modified zinc borate;

[0064] S2.2: Surface-modified zinc borate and polyethylene-vinyl acetate are put into a high-speed mixer at a mass ratio of 1:20, the vinyl acetate content in the polyethylene-vinyl acetate is 40%, and stirred at 65°C at a stirring speed of 240 rpm for 1.5 hours to obtain a high-viscosity antibacterial cross-linking agent.

[0065] S3: Current cross-linking compounding of adhesive

[0066] S3.1: The modified soybean meal, expanded graphite and high-viscosity antibacterial cross-linking agent were mixed and stirred at a mass ratio of 1:0.02:0.15, and the stirring speed was set to 250 rpm. Then, the mixture was placed in a rectangular container with a length, width and height of 20 cm, 10 cm and 10 cm respectively, and 316 stainless steel electrodes connected to the positive and negative poles of the power supply were installed on the inner walls of both sides. The power was turned on, and the voltage was increased to 30 V at a rate of 5 V / min and then maintained. The power was turned off and stirred for 15 seconds every 6 minutes, and then it was started again and powered on directly at a voltage of 30 V for 30 minutes to obtain cross-linked soybean meal.

[0067] S3.2: Mix 15 parts by weight of cross-linked soybean meal, 1 part by weight of inositol phosphate, 0.5 part by weight of sodium alginate and 1 part by weight of polyamide in a container, heat to 60°C, stir for 1 hour, then heat to 85°C, stir for 2 hours to obtain a formaldehyde-free flame retardant adhesive.

[0068] Based on the formaldehyde-free flame-retardant adhesive prepared by the method for preparing the formaldehyde-free flame-retardant adhesive, the present application provides a flame-retardant wooden board, comprising a substrate and a formaldehyde-free flame-retardant adhesive coated on the upper and lower surfaces of the substrate, wherein the substrate is a poplar veneer; the method for preparing the flame-retardant wooden board comprises the following steps:

[0069] Use manual gluing method to apply formaldehyde-free flame retardant adhesive at 200g / m 2 Apply glue to the upper and lower surfaces of the poplar veneer with a certain amount of glue. After the gluing is completed, leave it for 8 minutes, then assemble it with two poplar veneers on the outside and one poplar veneer on the inside, and then put it in a hot press for 10 minutes. The hot pressing temperature is 130℃ and the hot pressing pressure is 1.2MPa. After pressing, cool it for use.

[0070] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 removes step S1.1, replaces the high-strength modifier in step S1.2 with an equal mass of sodium dodecyl sulfate, and the remaining steps are the same as Example 1 to obtain a flame-retardant wooden board, which is recorded as Comparative Example 1.

[0071] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 removes step S3.1, and directly stirs the modified soybean meal, expanded graphite and high-viscosity antibacterial cross-linking agent at a mass ratio of 1:0.02:0.15 at 50°C to obtain cross-linked soybean meal. The remaining steps are the same as in Example 1 to obtain a flame-retardant wooden board, which is recorded as Comparative Example 2.

[0072] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 removes step S2.1 and replaces the surface-modified zinc borate in step S2.2 with zinc borate. The remaining steps are the same as Example 1 to produce a flame-retardant wooden board, which is recorded as Comparative Example 3.

[0073] Experiment 1: The flame retardant wood board prepared in the embodiment and comparative examples 1-3 were taken and performance tested according to the test requirements of GB / T11718-2009. All test samples were placed in an environment of 20°C and 65% humidity for 12 hours for equilibrium treatment before testing, and then cut into 5cm×5cm samples. The universal mechanical testing machine was used to test the bonding strength IB, the bonding strength 20°C IB after immersion in 20°C water for 6 hours, and the bonding strength 100°C IB after boiling in boiling water for 2 hours. Three samples were tested for each group of data, the average value was taken, and the data were calculated and recorded and tabulated, as shown in Table 1.

[0074] Table 1: Gluing strength of flame retardant panels

[0075] Bonding strength / MPa IB 20℃IB 100℃IB Example 1 1.91 1.75 1.03 Example 2 1.93 1.77 1.05 Example 3 1.96 1.79 1.08 Comparative Example 1 1.34 1.13 0.21 Comparative Example 2 1.32 1.09 0.25 Comparative Example 3 1.61 2.3 0.33

[0076] It can be seen from Table 1 that the bonding strength IB, 20℃ IB and 100℃ IB of the flame-retardant wood board prepared in the embodiment are all greater than those of comparative examples 1-3, which can prove that the preparation of a high-strength modifier and the modification of soybean meal particles can significantly enhance the bonding strength and waterproof performance of the formaldehyde-free flame-retardant adhesive when applied to plywood. It can also be proved that placing the modified soybean meal, expanded graphite and high-viscosity antibacterial cross-linking agent under electric current for cross-linking greatly improves the dry bonding strength and wet boiling water-resistant bonding strength of the subsequently prepared plywood. At the same time, it can be proved that the high-viscosity antibacterial cross-linking agent prepared by modifying zinc borate and polyethylene-vinyl acetate can improve the stability of the flame retardant system, thereby enhancing the bonding performance of the formaldehyde-free flame retardant adhesive.

[0077] Experiment 2: Take the flame-retardant wood board prepared in Example 1 and Comparative Example 3, and determine the flame retardant performance level of the flame-retardant wood board with reference to GB / T2408-2008, and determine the limiting oxygen index of the flame-retardant wood board with reference to GB / T2406-2008. Repeat the test three times and take the average value. Record the data and make a table, as shown in Table 2. It can be seen that the flame retardant performance and limiting oxygen index of the flame retardant wood board prepared in Example 1 are greater than those of Comparative Example 3, and a higher performance is achieved.

[0078] Table 2: Flame retardant properties of flame retardant boards

[0079] Flame retardant properties Limiting oxygen index / % Example 1 VTM-0 40 Example 2 VTM-0 41 Example 3 VTM-0 43 Comparative Example 3 VTM-1 31

[0080] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a formaldehyde-free flame retardant adhesive, characterized in that: The following steps are involved: S1: Modification of soy protein Divinylbenzene and itaconic anhydride are mixed, and then isoamyl acetate is added and stirred, and then azobisisobutyronitrile is added and nitrogen is introduced, and then the mixture is heated for reaction and then centrifuged to obtain a solid substance, and then the solid substance is washed and dried to obtain a high-strength modifier, and the soybean meal is ultrafinely ground to obtain soybean meal particles, and the high-strength modifier and deionized water are added to a container equipped with a stirring device and a condensing device, and then ammonia water is added, and then the soybean meal particles are added after stirring, and nitrogen is introduced in a stirring state, and then the mixture is heated and stirred to obtain modified soybean meal; S2: Preparation of highly viscous antibacterial crosslinkers Put titanium acetylacetonate in a container, add toluene and stir, then add zinc borate powder, heat and stir, and then perform rotary evaporation to obtain surface-modified zinc borate, put the surface-modified zinc borate and polyethylene-vinyl acetate into a high-speed mixer, heat and stir, and obtain a high-viscosity antibacterial cross-linking agent; S3: Current cross-linking compounding of adhesive The modified soybean meal, expanded graphite and high-viscosity antibacterial cross-linking agent are mixed evenly, then placed in a container equipped with electrodes, powered on, and alternately powered on and stirred at a fixed frequency to obtain a cross-linked soybean meal. The cross-linked soybean meal, inositol phosphate, sodium alginate and polyamide are mixed and placed in a container, and heated and stirred for a second time to obtain a formaldehyde-free flame retardant adhesive.

2. The method for preparing a formaldehyde-free flame retardant adhesive according to claim 1, characterized in that: Step S1: modification of soybean protein, comprising the following steps: S1.1: Divinylbenzene and itaconic anhydride containing 0.1-0.15wt% of tert-butylcatechol as a stabilizer are mixed in a mass ratio of 1:(0.8-0.9) in a container, and then 2-3 times the mass of isoamyl acetate is added and stirred evenly, and then 1-2wt% of azobisisobutyronitrile is added and nitrogen is introduced for 25-30 minutes, and then reacted at 70-75°C for 10-12 hours, and solid matter is obtained after centrifugation, washed with isoamyl acetate 2-3 times and then with petroleum ether 2-3 times, and then dried in a vacuum drying oven at 40-45°C to constant weight to obtain a high-strength modifier; S1.2: The soybean meal is placed in an ultrafine grinder and crushed to a particle size of 10-20 μm to obtain soybean meal microparticles. 2-3 parts by weight of a high-strength modifier and 40-50 parts by weight of deionized water are added to a container equipped with a stirring device and a condensing device, and then 0.6-0.9 parts by weight of ammonia water are added. After stirring for 20-30 minutes, 9-12 parts by weight of soybean meal microparticles are added. Nitrogen is bubbled through the mixture under stirring for 20-25 minutes. The mixture is then heated to 60-65°C and stirred at a stirring speed of 200-300 rpm for 2-3 hours to obtain modified soybean meal.

3. The method for preparing a formaldehyde-free flame-retardant adhesive according to claim 2, characterized in that: Step S2: Preparation of a highly viscous antibacterial cross-linking agent, comprising the following steps: S2.1: 0.2-0.3 parts by weight of titanium acetylacetonate is placed in a container, 6-8 parts by weight of toluene is added and stirred for 20-30 minutes, then 3-4 parts by weight of zinc borate powder is added, heated to 40-50° C. and stirred for 30-35 minutes, then placed in a rotary evaporator at a temperature of 70-75° C. to evaporate and remove the toluene, to obtain surface-modified zinc borate; S2.2: Place the surface-modified zinc borate and polyethylene-vinyl acetate in a mass ratio of 1:(20-30) into a high-speed mixer, stir at 60-65° C. and a stirring speed of 180-240 rpm for 1-1.5 hours to obtain a high-viscosity antibacterial cross-linking agent.

4. The method for preparing a formaldehyde-free flame-retardant adhesive according to claim 3, characterized in that: Step S3, current cross-linking and compounding of the adhesive, comprises the following steps: S3.1: The modified soybean meal, expanded graphite and high-viscosity antibacterial cross-linking agent are mixed and stirred uniformly at a mass ratio of 1: (0.02-0.03): (0.15-0.2), and the stirring speed is set to 220-250rpm. Then, the mixture is placed in a container, and a power supply is turned on. The voltage is increased to 25-30V at a rate of 3-5V / min, and the voltage is maintained. The power supply is turned off and stirred for 10-15S every 4-6 minutes, and then the power supply is turned on again and directly energized at a voltage of 25-30V for 25-30 minutes to obtain a cross-linked soybean meal. S3.2: Mix 15-20 parts by weight of cross-linked soybean meal, 1-2 parts by weight of inositol phosphate, 0.5-1 parts by weight of sodium alginate and 1-1.2 parts by weight of polyamide in a container, heat to 50-60°C, stir for 0.5-1 hour, then heat to 80-85°C, stir for 1-2 hours to obtain a formaldehyde-free flame retardant adhesive.

5. The method for preparing a formaldehyde-free flame-retardant adhesive according to claim 2, characterized in that: The soybean meal in step S1.2 is the product obtained by hot pressing soybeans to extract oil.

6. The method for preparing a formaldehyde-free flame-retardant adhesive according to claim 3, characterized in that: The vinyl acetate content of the polyethylene-vinyl acetate in step S2.2 is 40-45%.

7. The method for preparing a formaldehyde-free flame-retardant adhesive according to claim 4, characterized in that: The container in step S3.1 is a rectangular parallelepiped with a length, width and height of 20 cm, 10 cm and 10 cm respectively. 316 stainless steel electrodes are installed on the inner walls on both sides, which are connected to the positive and negative poles of the power supply respectively.

8. A formaldehyde-free flame retardant adhesive, characterized in that: The adhesive is prepared by the method for preparing a formaldehyde-free flame retardant adhesive according to any one of claims 1 to 7.

9. A flame retardant wood board, characterized in that: The invention comprises a substrate and a formaldehyde-free flame retardant adhesive coated on the upper and lower surfaces of the substrate, wherein the substrate is a poplar veneer, and the formaldehyde-free flame retardant adhesive is prepared by the preparation method of the formaldehyde-free flame retardant adhesive according to any one of claims 1 to 7.

10. A method for preparing the flame-retardant wood board according to claim 9, characterized in that: The following steps are involved: Use manual gluing method to apply formaldehyde-free flame retardant adhesive at 200g / m 2 Apply glue to the upper and lower surfaces of the poplar veneer with a certain amount of glue. After the gluing is completed, leave it for 8 minutes, then assemble it with two poplar veneers on the outside and one poplar veneer on the inside, and then put it in a hot press for 10 minutes. The hot pressing temperature is 130℃ and the hot pressing pressure is 1.2MPa. After pressing, cool it for use.

Citation Information

Patent Citations

  • Adhesive for artificial board and preparation method of adhesive

    CN105153998A

  • Environment-friendly two-component EVA adhesive and preparation method, application and packaging product thereof

    CN112760061A

  • Phytic acid / polydopamine composite flame-retardant polyamide 6 and preparation method thereof

    CN113045891A

  • Adhesive as well as preparation method and application thereof

    CN116376483A

  • Composite bio-based flame-retardant non-woven fabric and preparation method thereof

    CN116752347A